Presencia de Hemoparásitos en perros mediante la realización de frotis sanguíneo en la localización el porvenir de la Parroquia San Carlos Cantón Quevedo. - Coello Ormaza, Julissa Liseth (2025)
The present work will seek to observe the presence of emo parasitosis in canines by performing blood smears from the Quevedo canton located in the San Carlos parish. How do we know that emo parasitosis is a disease that is transmitted through the bite of a tick within the diseases The most common that our canines can present is Babesia canis and Ehrlichia canis, which are diseases that mainly affect the blood cells, in this case the red blood cells where they can cause very strong injuries. Also bleeding, whether internal or external, in addition to causing anemia and anorexia, if not treated over time, this problem can trigger a number of diseases. The percentage descriptive method was used where samples were taken from 50 canines found in the future of the San Carlos Cantón Quevedo Parish. Where there was the presence of 30%, the genus of hemoparasite with the most prevalence was Ehrlichia canis with 47% equivalent to 7 positive cases, followed by the genus Babesia canis with 33% equivalent to 5 positive cases, and lastly Anaplasma platys with 20% equivalent to 3 cases. The identification of Hemoparasites according to sex is 52% in males and 48% in females. According to age, there was a higher prevalence in dogs from 1 to 4 years old with 46% and a smaller number in dogs from 9 to 13 years old with 8%. The identification of hemoparasites according to the breed reached a conclusion where mixed-breed canines were the most affected with 54% and in lower prevalence breeds such as pit bull 12%, labrador 8%, french 6%, chihuahua 2% among others were found.